2022
DOI: 10.1007/s10853-022-06991-6
|View full text |Cite
|
Sign up to set email alerts
|

Advanced structural analysis of a laser additive manufactured Zr-based bulk metallic glass along the build height

Abstract: Additive manufacturing of bulk metallic glasses (BMGs) has opened this material class to an exciting new range of potential applications, as bulk-scale, net-shaped amorphous components can be fabricated in a single step. However, there exists a critical need to understand the structural details of additive manufactured BMGs and how the glassy structure is linked to the mechanical properties. Here, we present a study of structure and property variations along the build height for a laser powder bed fusion (LPBF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…Recent research demonstrated that the bottom parts of the printed samples are built with higher cooling rates, resulting in a softer microstructure. [ 117 ] It follows that the reduced reheating and heat accumulation during the procedure, as previously indicated, results in the softer structure of SB samples.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Recent research demonstrated that the bottom parts of the printed samples are built with higher cooling rates, resulting in a softer microstructure. [ 117 ] It follows that the reduced reheating and heat accumulation during the procedure, as previously indicated, results in the softer structure of SB samples.…”
Section: Discussionmentioning
confidence: 66%
“…In the literature it was reported that the bottom part of printed Zr‐based samples exhibits larger MRO sizes as a result of faster cooling rates. [ 117 ] Therefore, it can be concluded that the higher MRO size in SB materials is due to the reduced reheating and probably heat accumulation during the process.…”
Section: Discussionmentioning
confidence: 99%
“…EDP2PDF is of interest for studying a wide range of materials and has been used in recent studies of various bulk metallic glasses (Nomoto et al, 2021(Nomoto et al, , 2022Best et al, 2022).…”
Section: Program Designmentioning
confidence: 99%
“…7. Thus, as in our previous work [54,59], each lamella was assumed to have the average hardness of the surrounding four indentations. The calculated MRO cluster size and volume fraction from each lamella and the corresponding hardness values are shown in Table 5.…”
Section: Effects Of Elastostatic Compression For Controlled Initial S...mentioning
confidence: 99%